Decentralisation and local governance in Mozambique: the challenges of promoting bottom-up dynamics from the top down. Issue 2 (3rd March 2016) - Holanda Maschietto, Roberta
Abstract: Since the conclusion of the peace accords in 1992, Mozambique has undergone several changes in the field of governance and institution-building. One key aspect of such reforms, strongly promoted by donors in peace-building contexts, has been the agenda of decentralisation and local governance, which has entailed political devolution in selected municipalities, and deconcentration and the creation of local councils in the rural districts. This article examines this agenda and its implementation focusing on two domains. First, it discusses the different interests that have shaped the political decisions taken on this agenda at the national level. Second, it examines the case of the local councils in the district of Angoche, critically debating the extent to which they epitomise the increase of local representativeness and, thus, whether or not they enhance bottom-up dynamics of governance. I argue that the limited effectiveness of such reforms in Mozambique reflect the inherent contradiction between the strong top-down dynamics that shape this process and the bottom-up effects that it aims to promote.